2013
DOI: 10.1002/cncy.21324
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 1 protein detected by enzyme‐linked immunosorbent assay and immunocytochemistry

Abstract: BACKGROUND: Glucose transporter 1 (GLUT1) is a hallmark of metabolic change in cancer cells. The objective of this study was to determine the role of GLUT1 protein in diagnosing malignant pleural effusions by enzyme-linked immunosorbent assay (ELISA) and immunocytochemistry. METHODS: In total, 82 pleural effusions were collected and classified as benign (n 5 42), atypical (n 5 8), or malignant (n 5 32) based on cytologic diagnosis and etiology. GLUT1 protein levels in effusions were measured by ELISA. GLUT1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Liao et al studied glucose transporter 1(GLUT 1) expression, which is a hallmark metabolic change in cancer cells, using immunocytochemistry on cell blocks in benign, atypical, or malignant pleural eff usions. Th ey determined that malignant eff usion cell blocks were positive for GLUT 1 expression in 84.4% of cases with a 100% specifi city and 93.2% accuracy (25). Khoor et al evaluated the expression of TTF-1 on cell blocks in malignant pleural eff usions, 26 pulmonary adenocarcinomas, 26 non-pulmonary adenocarcinomas and 4 malignant mesotheliomas.…”
Section: Türk Patoloji Dergisi/turkish Journal Of Pathology Köksal D mentioning
confidence: 99%
“…Liao et al studied glucose transporter 1(GLUT 1) expression, which is a hallmark metabolic change in cancer cells, using immunocytochemistry on cell blocks in benign, atypical, or malignant pleural eff usions. Th ey determined that malignant eff usion cell blocks were positive for GLUT 1 expression in 84.4% of cases with a 100% specifi city and 93.2% accuracy (25). Khoor et al evaluated the expression of TTF-1 on cell blocks in malignant pleural eff usions, 26 pulmonary adenocarcinomas, 26 non-pulmonary adenocarcinomas and 4 malignant mesotheliomas.…”
Section: Türk Patoloji Dergisi/turkish Journal Of Pathology Köksal D mentioning
confidence: 99%
“…In summary, the expression of GLUT1 may be regard as a potential marker of malignant tumors. Some authors have also examined the use of GLUT1 as a marker to detect malignant cells in serous effusions and with resemble results 19,20 . In present study, we investigated GLUT1 reactivity by ICC in serous effusion cell blocks and the result showed that the positive composition were 168 of 183 malignant effusions, 5 of 95 benign effusions, the sensitivity and specificity were 91.8% and 94.7%, respectively.…”
Section: Discussionmentioning
confidence: 72%